2020
DOI: 10.1155/2020/1908392
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sexually Transmitted Infections in Pregnant Adolescents on Preterm Birth and Chorioamnionitis

Abstract: Background. Adolescents have an increased risk of preterm birth (PTB) and sexually transmitted infections (STIs). We examined the prevalence and impact of STIs (gonorrhea, chlamydia, and trichomonas) on PTB and chorioamnionitis in pregnant adolescents. Methods. This retrospective cohort study utilized the first pregnancy delivered at an urban hospital among patients≤19 years old over a 5-year period. Poisson regression with robust standard errors was used to estimate prevalence ratios (PR) and 95% confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…But our study has several limitations. First, the lack of data about sexually transmitted infections (STIs), which is reported to be a risk factor for PTB in the context of vaginal microbiota [ 21 ]. Second, the lack of performing GBS serotyping.…”
Section: Discussionmentioning
confidence: 99%
“…But our study has several limitations. First, the lack of data about sexually transmitted infections (STIs), which is reported to be a risk factor for PTB in the context of vaginal microbiota [ 21 ]. Second, the lack of performing GBS serotyping.…”
Section: Discussionmentioning
confidence: 99%
“…25,47 Similarly, Mullick et al 97 demonstrated a higher incidence of low birth weight and preterm delivery in pregnant women infected with T. vaginalis. In a recent study by Fuchs et al, 84 it was reported that adolescents diagnosed with T. vaginalis during pregnancy had more than a twofold increased likelihood of chorioamnionitis compared to those not diagnosed with T. vaginalis.The C. trachomatis infection in the third trimester of pregnancy was associated with more than a twofold increased likelihood of preterm birth when compared to participants without C. trachomatis during pregnancy. 84 A 2015 meta-analysis of M. genitalium infection in pregnant women reported an approximately twofold increase in the odds of preterm delivery or spontaneous abortion in women with this STI.…”
Section: Untreated Sexually Transmitted Infections Are Associated With Adverse Pregnancy and Neonatal Outcomesmentioning
confidence: 96%
“…In a recent study by Fuchs et al, 84 it was reported that adolescents diagnosed with T. vaginalis during pregnancy had more than a twofold increased likelihood of chorioamnionitis compared to those not diagnosed with T. vaginalis.The C. trachomatis infection in the third trimester of pregnancy was associated with more than a twofold increased likelihood of preterm birth when compared to participants without C. trachomatis during pregnancy. 84 A 2015 meta-analysis of M. genitalium infection in pregnant women reported an approximately twofold increase in the odds of preterm delivery or spontaneous abortion in women with this STI. 98 Furthermore, a recent study conducted by Smullin et al 60 in South Africa reported an association between M. genitalium and adverse pregnancy outcomes in HIV-infected pregnant women.…”
Section: Untreated Sexually Transmitted Infections Are Associated With Adverse Pregnancy and Neonatal Outcomesmentioning
confidence: 96%
See 1 more Smart Citation
“…46 Another retrospective cohort study also failed to demonstrate a relationship between preterm delivery and gonorrhea despite finding a trend toward chorioamnionitis during the third trimester of pregnancy with gonorrhea. 47 These findings suggest that gonorrhea's role in inducing chorioamnionitis is time-specific.…”
Section: Gonorrheamentioning
confidence: 96%